Identifying Endometrial Delay Improves Treatment Outcome in Women with Thin Endometrium and Infertility - Narangerel Namshir; Yanjinsuren Darmaa; Munkhtsetseg Davaatseren; Bum Chae Choi (Central Asian Journal of Medical Sciences)
Objective: To determine the impact of endometrial delay on reproductive outcomes.